Enhancing chemical safety in manufacturing: Lessons from major chemical spill incidents and the role of ergonomics - Yee, L. C.; Shalini, Murugan; Lim, W. Y. (Penerbit UMP, 2025)
Chemical spills in manufacturing industries pose serious dangers to the safety of the environment, the health of employees, and the effectiveness of operations. This study examines the root causes and effects of significant chemical spill incidents. The analysis focuses on the lessons learned from these incidents, ergonomic and safety issues, and missed preventive measures. The thorough evaluation emphasizes how weak safety measures and poor ergonomic practices contribute to the rise of such incidents. The proposed alternative solutions focus on integrating chemical safety measures with ergonomic principles to reduce hazards and improve worker safety. The findings help to create safer industrial settings by providing industries with insights to prevent future chemical accidents and enhance worker well-being and operational sustainability.